Dinosaur tracks at Cañadón de las Campanas and Villa El Chocón area (Late Cretaceous, Candeleros Formation), Patagonia, Argentina - Krapovickas, Verónica (2020)
Several locations are known along the coast of the Ezequiel Ramos Mexía Dam, Neuquén province in Northwestern Argentinian Patagonia, comprising one of the richest dinosaur-tracking areas in South America. In this contribution we study a total of 166 dinosaur footprints and 31 dinosaur trackways recorded at the base of the Candeleros Formation (Cenomanian) from a new tracksite - Cañadón de las Campanas - and other localities nearby the Villa El Chocón area. The dinosaur footprints identified correspond to six morphotypes assigned to two ichnotaxa and three others are left with open nomenclature: Bressanichnus patagonicus, cf Brontopodus isp. (Sauropodichnus giganteus), large U-shaped tridactyl footprints (Limayichnus major), medium-siz ed tridactyl footprints and smallsized tridactyl footprints. The ichnotaxa S. giganteus and L. major are considered nomen dubium. Particularly, B. patagonicus presents two morphologies at the posterior margin of the footprint (rounded and narrow) most likely related to varying gaits and/or changingbehavior. As a result, the herein presented ichnofauna is interpreted as produced by non-avian theropod of varied sizes (large sized = large U-shaped tridactyl footprints, medium to large size = B. patagonicus, medium size = medium-sized tridactyl footprints and small size = small-sized tridactyl footprint) and one large-sized sauropod dinosaur (cf. Brontopodus isp.).